METODE TALKING STICK DENGAN MEDIA AUDIO UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN STENOGRAFI - Wahyuni Sri Utami (Dinamika Pendidikan)
Stenography learning in class X Office Administration 3 at SMK Negeri 1 Pemalang indicated the low learning motivation. The purpose of this research was to know the students’ learning motivation improvement after using talking stick method with audio media at Stenography subject in class X Office Administration at SMK N 1 Pemalang. It was a classroom action research conducted in three cycles which each cycle was consisted of planning, implementation, observation, and reflection. The data were collected by observation and test. Then, the data were analyzed by percentage descriptive. The results showed that talking stick method with audio media can improve students' motivation at Stenography subject in class X Office Administration 3 at SMK N 1 Pemalang. The average of students’ motivation on the first cycle was 63.08%, then increased up to 72.08% on the second cycle and finally, it went up to 85.08% on the third cycle.